Aspects of fire damage to low rise housing - Reid, Lindsay (University of Edinburgh, 1988)
The purpose of this Thesis is to consider reasonable options for reducing the fire damage in low rise housing. Fires in dwellings account for a large number of fires occuncing within the U. K. In terms of financial. loss dwelling fires are not of such great concern as are the fires in other occupancy groups, namely industrial. It is perhaps for this reason that dwelling fires have received little research attention in the past. With regard to fatalities, dwelling fires are extremely important as the large proportion of people who die in fire do so in the home. Because of the high risk of death from a domestic fire it has been necessary to consider the effect that the options for reducing property damage will have on life. The effect that the occupants have on the options has also been considered. The first section examines the fire problem whilst the second section discusses the options which could be used to reduce fire damage. These measures include modifying the construction, furniture and furnishings, domestic appliances, education and publicity campaigns, and active fire protection systems. The main conclusions reached are (when cost and practical difficulties are considered ) that education and publicity campaigns, improvements in the fire behaviour of furniture and fittings (including lightweight internal doors), and fire detectors are likely to achieve the greatest impact on fire damage reduction. Due to economic constraints only token efforts to reduce fire damage may be exercised and this will not be enough to make any significant reduction in either the frequency or the severity of domestic fires. A serious effort is required to reverse, or at least halt, the growth in dwelling fires.
Keywords: Engineering; Safety; measures; Fires; Housing